Perancangan Pengenalan Denah Kampus Institut Teknologi Telkom Purwokerto berbasis Flash - Alwi Sahrul Al Falah; Bryan Ade Bandaso; Candra Taufik Kustiyono; Favian Yumna; Gibran Muchtazar. M. Dien (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
The development of technology, information and communication is growing very quickly so that it has an impact on humans, including in the world of education. With the rapid growth in the world of education, especially in higher education. The problem is always the same when a new teaching will take place where new students and lecturers are often late because they are not too familiar with the campus plan. With the development of Internet and multimedia technology, Flash animation as one of the most popular multimedia resources has shown explosive growth. Macromedia Flash is a software for interactive learning media so that it can improve student achievement. By using the survey method to collect data. So from the results of the study it can be concluded that the application of the campus plan of the Telkom Purwokerto Institute of Technology is designed for people who are interested in the Telkom Purwokerto Institute of Technology Campus to see the campus floor plan before visiting. From the development of interactive multimedia applications, it turns out to be quite helpful for people who want to know the campus plan of the Telkom Purwokerto Institute of Technology. So that the use of interactive multimedia is interesting, people will be interested in using the application or even interested in coming to the place.